<DATA REPORT>RECORDS OF RADIO AURORA AT SYOWA STATION, ANTARCTICA IN 1995 and 1996 - INAMORI, Koji; OHTAKA, Kazuhiro; IGARASHI, Kiyoshi (National Institute of Polar Research, 1997)
P(論文) departmental bulletin paper